2014
DOI: 10.1016/j.jaci.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibition abrogates aeroallergen-induced immune tolerance by suppressing prostaglandin I2 receptor signaling

Abstract: Background The prevalence of allergic diseases doubled in developed countries in the last several decades. Cyclooxygenase (COX) inhibiting drugs augmented allergic diseases in mice by increasing allergic sensitization and memory immune responses. However, whether COX inhibition can promote allergic airway diseases by inhibiting immune tolerance is not known. Objective To determine the role of the COX pathway and PGI2 signaling through the PGI2 receptor (IP) in aeroallergen-induced immune tolerance. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…In this in vivo model, iloprost-treated DCs downregulated Th2 differentiation from naive T cells and were also unable to boost effector cytokine production in primed Th2 cells (14). Furthermore, PGI2 was critical to immune tolerance induced by mucosal exposure to antigen in an mouse model of allergic airway inflammation (49). Although these studies revealed that PGI 2 has important immunomodulatory effects on DCs and T cells, our novel results indicate that PGI 2 has profound effects on ILC2 cytokine protein expression and the number of ILC2s in the lung following acute allergen-challenge without sensitization.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this in vivo model, iloprost-treated DCs downregulated Th2 differentiation from naive T cells and were also unable to boost effector cytokine production in primed Th2 cells (14). Furthermore, PGI2 was critical to immune tolerance induced by mucosal exposure to antigen in an mouse model of allergic airway inflammation (49). Although these studies revealed that PGI 2 has important immunomodulatory effects on DCs and T cells, our novel results indicate that PGI 2 has profound effects on ILC2 cytokine protein expression and the number of ILC2s in the lung following acute allergen-challenge without sensitization.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, an IP antagonist increased eosinophil adhesion to endothelial cells (48). In the ovalbumin model, IP 2/2 mice had significantly augmented pulmonary proinflammatory Th2 cytokine expression, airway mucus, and airway responsiveness compared with WT mice in both acute and chronic allergen-induced inflammation models (17,18,49).…”
Section: Discussionmentioning
confidence: 99%
“…Andererseits kann es aber auch zusätzlich die entzündungsauflösende Phase des Infekts initiieren (Shinomiya et al 2001). Prostaglandin I2 scheint einen bronchoprotektiven, antiinflammatorischen und antiallergischen Effekt zu haben, der durch COX-Hemmer aufgehoben wird (Zhou et al 2014) (s. 7 Abschn. 7.2.3).…”
Section: Prostaglandin I2unclassified
“…In der vorher erwähnten Studie von Zhou et al (2014) Inhalation von PGE2 vor Allergen-Challenge reduzierte bei allergischen Asthmatikern sowohl die Früh-als auch die Spätantworten auf das inhalierte Allergen (Pavord und Tattersfield 1995), unterdrückte die Allergen-induzierte eosinophile Inflammation sowie die bronchiale Hyperreaktivität (Gauvreau et al 1999). Ebenfalls nach Inhalation von PGE2 beobachtete man eine Reduktion von PGD2, jenem Prostaglandin, das durch Mastzellenaktivierung sezerniert wird.…”
Section: Tete Inwieweit Cox-hemmer Die Bildung Von Lipoxinen Hemmenunclassified